PENINGKATAN KEMAMPUAN MENULIS PANTUN DENGAN MENGGUNAKAN TEKNIK JEJAKA SISWA KELAS IV SDN 003 SUNGAI SALAK KECAMATAN TEMPULING - amir hakim harahap (Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir Riau, 2021)
Abstract The problem of Classroom Action Research (PTK) is the low learning outcomes of Indonesian in poetry writing material for Grade IV students of SDN 003 Sungai Salak, Tempuling Regency. achieved by students, 70. Pantun is written by students of plagiarism or rhymes created by others. Nobody writes poetry with their own work. This learning problem was overcome by using the Acronym Technique of Exploration Words Exploration: problem formulation Is the application of the Trace Technique able to improve students' writing skills in Class IV SDN 003 Sungai Salak, Tempuling Regency? This study aims to improve Indonesian language learning outcomes in rhyming writing material. This research is expected to be useful for students, teachers, the community, and the Indragiri Hilir Regency Education Office. Based on the results of research Learning conducted using youth techniques has significantly improved learning outcomes. In the pre-cycle no students had finished learning (0%); in the first cycle with undergraduate techniques 4 students (18.18%) completed learning with an average grade of 47.30 (less category); and in cycle II as many as 20 students (90.90%) had completed their studies with an average grade of 82.27, (Good category). Based on research results increasing learning with young techniques succeeded in increasing the problem of low poetry writing skills of Class IV SDN 003 Sungai Salak students, Tempuling Regency. Students have been able to understand and create poetry with their own work. Abstrak Permasalahan Penelitian Tindakan Kelas (PTK) ini adalah dari rendahnya hasil belajar Bahasa Indonesia pada materi menulis pantun siswa Kelas IV SDN 003 Sungai Salak Kecamatan Tempuling, Ini terlihat dari hasil belajar, tidak ada siswa (0%) yang mencapai target minimal hasil belajar yang harus dicapai siswa, 70. Pantun yang ditulis siswa plagiat atau pantun ciptaan orang lain. Tidak ada seorang pun yang menulis pantun dengan karya sendiri. Masalah belajar ini diatasi dengan menggunakan Teknik Jejaka akronim dari Jelajah Sajak kata: rumusan masalah Apakah penerapan Teknik Jejaka dapat meningkatkan kemampuan menulis pantun siswa Kelas IV SDN 003 Sungai Salak Kecamatan Tempuling? Penelitian bertujuan untuk untuk meningkatkan hasil belajar Bahasa Indonesia materi menulis pantun. Penelitian diharapkan bermanfaat bagi siswa, guru, masyarakat, dan Dinas Pendidikan Kabupaten Indragiri Hilir. Berdasarkan hasil penelitian Pembelajaran yang dilaksanakan dengan menggunakan teknik jejaka berhasil meningkatkan hasil belajar secara signifikan. Pada prasiklus tidak ada siswa yang tuntas belajar (0%) ; pada siklus I dengan teknik jejaka 4 siswa (18,18%) tuntas belajar dengan nilai rata-rata 47,30 (kategori Kurang); dan pada siklus II sebanyak 20 siswa (90,90%) telah tuntas belajar dengan nilai rata-rata kelas 82,27, (kategori Baik). Berdasarkan hasil penelitian perbaikan pembelajaran dengan teknik jejaka berhasil memperbaiki masalah rendahnya kemampuan menulis pantun siswa Kelas IV SDN 003 Sungai Salak Kecamatan Tempuling. Siswa-siswa telah dapat memahami dan mencipta pantun dengan karya sendiri.